2008
DOI: 10.1021/jf802429x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activities of Novel Pyrazole Oxime Derivatives Containing a 2-Chloro-5-thiazolyl Moiety

Abstract: A series of novel pyrazole oxime derivatives containing a 2-chloro-5-thiazolyl moiety were synthesized. Their structures were confirmed by (1)H NMR, (13)C NMR, and elemental analysis. The preliminary bioassays showed that all of the title compounds had low acaricidal activity against Tetranychus cinnabarinus . However, most of them exhibited excellent insecticidal activity against Aphis medicagini at the dosage of 0.5 mg/mL, and some compounds still showed good insecticidal activity against A. medicagini even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
48
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 27 publications
0
48
0
2
Order By: Relevance
“…[9][10][11] For thus, pyrazole derivatives have attracted considerable attention in the recent years for their diverse biological activities. [12][13][14][15][16][17] In this paper, the novel 1,1'-(5,5'-(1,3-phenylene)bis(3-aryl-4,5-dihydro-1H-pyrazole-5,1-diyl))diethanone (5a-e) and 1,3-bis(1-phenyl-3-(aryl)-4,5-dihydro-1H-pyrazol-5-yl)benzene (6a-e) were synthesized in good yields and evaluated the antibacterial activities of compounds (5a-e) against some human pathogenic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] For thus, pyrazole derivatives have attracted considerable attention in the recent years for their diverse biological activities. [12][13][14][15][16][17] In this paper, the novel 1,1'-(5,5'-(1,3-phenylene)bis(3-aryl-4,5-dihydro-1H-pyrazole-5,1-diyl))diethanone (5a-e) and 1,3-bis(1-phenyl-3-(aryl)-4,5-dihydro-1H-pyrazol-5-yl)benzene (6a-e) were synthesized in good yields and evaluated the antibacterial activities of compounds (5a-e) against some human pathogenic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…To innovations in biotechnology for sustainable development of agriculture belongs the elaboration of new PGRs on the basis of low molecular weight synthetic heterocyclic compounds (LMWHC), derivatives of pyridine, pyrimidine, pyrazole, triazine, and oxazole to intensify plant growth and development, and increase crop productivity. As is known LMWHC are widely used in the medicine as drugs for the treatment of bacterial, infectious, viral, fungal, inflammatory, neural, allergic, cancer, and autoimmune diseases [42][43][44][45][46][47][48][49][50][51][52][53][54][55], and in the agriculture as PGRs, herbicides, fungicides, insecticides, acaricides, and antibacterial agents [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71]. Our numerous works devoted to study of plant growth regulatory activity of LMWHC, synthesized in the Institute of Bioorganic Chemistry and Petrochemistry of NAS of Ukraine, showed that different classes of LMWHC used at very low non-toxic for human health and environment concentrations 10 -8 M -10 -9 M revealed the broad spectrum of biological action on various crops [72][73][74][75] …”
Section: Introductionmentioning
confidence: 99%
“…Pyrazole oximes are an important class of heterocyclic compounds which have drawn intense attention because of their good fungicidal [1,2], insecticidal [3][4][5], acaricidal [6], and anti-tobacco mosaic virus (TMV) activity [7]. For instance, Fenpyroximate (Figure 1), a potent agricultural acaricide with a vital pyrazole oxime backbone in the structure, possesses wonderful acaricidal property against some phytophagous mites such as Polyphagotarsonemus latus Banks and Tetranychus urticae Koch on different crops [8].…”
Section: Introductionmentioning
confidence: 99%